Levels of comprehensive language development in children from second to sixth grade of elementary school - Tapia Mendieta, Violeta (2000)
The article analizes the quantitative characteristics of the language proficiency on a sample of 541 elementary students from second to sixth degree of Lima Metropolitana. Percentile ranks related to the total score, areas and subtests of the Woodcock Language Proficiency Battery are presented.